TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, QUALITY ASSURANCE, AND ORGANIZATIONAL PERFORMANCE: CASE STUDY IN ISLAMIC HIGHER EDUCATION INSTITUTIONS (IHEIS) - Hambali, Muh.; Idris, Idris (Universitas Brawijaya, Indonesia, 2020)
This study aims to examine the relationship between transformational leadership, organizational culture, quality assurance, and organizational performance. It also examined the mediating effect of quality assurance in the relationship between transformational leadership and organizational performance, and between organizational culture and organizational performance. The instruments in the form of Google forms were distributed to employees who work in quality assurance units in several public and private Islamic higher education institutions for 6 months, June-December 2019. 128 Data were processed and analyzed out of 135 data collected. The five-point Likert scale was used to assess the variables and to measure the items. Furthermore, Partial Least Square (PLS) was used to test the proposed hypotheses. This study found that the relationship between transformational leadership and organizational performance both directly and indirectly through quality assurance was not significant. Transformational leadership also did not affect quality assurance. On the other hand, organizational culture was proven to be able to influence high organizational performance and quality assurance. Besides, quality assurance could not mediate the relationship between transformational leadership and organizational performance, but it can positively and significantly mediate in the relationship between organizational culture and organizational performance. The results provided by this study provide the understanding and linking among transformational leadership, organizational culture, quality assurance, and organizational performance among Islamic higher education institutions (IHEIs). While the extent of leadership research has conducted in manufactures organizations, this study shifted the focus of attention to the religious-based institutions (IHEIs).